Nematicidal Activity of Lantana Camara L. for Control of Root-Knot Nematodes - Ghimire, Ganesh; Gupta, Ranjana; Keshari, Arvind K (Nepalese Journal of Zoology, 2015)
Various concentrations of aqueous leaf extract of Lantana camara L. were assessed against second stage juveniles (J2) of Meloidogyne spp. (Goeldi, 1982) for its nematicidal potency in vitro conditions. Study showed 50% concentration of Lantana camara leaf extract at 48 hrs of incubation period and above showed effective in immobilizing second stage of larvae (J2) of Meloidogyne spp. The standard concentration ‘S’ (100%) of leaf extract was found to be highly nematostatic, 98.66% of nematode were found dead in 48 hrs. Similarly, 57.66% of nematode juveniles were found dead when applied 50% concentration in 48 hrs. Mean number of (J2) dead at 100% concentration for three time period was statistically significant highest at 48 hrs. So far, 50% concentration in 48 hrs and above was appropriate for controlling the root-knot nematode which seems as an alternative to chemical pesticides.